The Boey Score as a Quick Assessment Tool in the Prediction of Postoperative Mortality in Patients with Hollow Viscus Perforation: A Study in Karachi, Pakistan - Seriwala, Haseeb Munaf; Zia, Maria (Biological and Clinical Sciences Research Journal, 2025)
Hollow viscus perforation (HVP) is a surgical emergency with significant morbidity and mortality. The Boey score, incorporating preoperative shock, medical comorbidities, and delay in surgical intervention, serves as a predictive model for postoperative outcomes. Early identification of high-risk patients through this scoring system may assist in optimizing treatment approaches and improving survival rates. Objective: To determine the frequency of mortality in patients with hollow viscus perforation according to their Boey score. Methods: This descriptive cross-sectional study was conducted at the Department of Surgery, Dr. Ruth K. M. Pfau Civil Hospital, Karachi, from July 2024 to January 2025. After ethical approval, 185 patients aged >18, of either gender, presenting with a confirmed diagnosis of HVP, were enrolled via non-probability consecutive sampling. Data were collected on demographic variables, clinical parameters, Boey score components, and outcomes. Statistical analysis was performed using SPSS version 25. Chi-square tests assessed associations between mortality and patient characteristics; a p-value <0.05 was considered statistically significant. Results: Out of 185 patients, mortality was observed in 21 cases (11.35%). Age and gender showed no statistically significant association with mortality (p = 0.55 and p = 0.197, respectively). However, a statistically significant relationship was found between delayed presentation (>24 hours) and increased mortality (p = 0.034). Among patients presenting within 24 hours, only 3 out of 65 died, whereas in those presenting after 24 hours, 18 out of 120 died. The Boey score effectively stratifies patients based on risk, with higher scores correlating with higher mortality. Conclusion: The Boey score is a reliable prognostic tool for assessing mortality risk in patients with hollow viscus perforation. Delayed presentation significantly increases mortality, emphasizing the need for prompt diagnosis and intervention.